SOSIALISASI PERAN PEREMPUAN DALAM PENGENTASAN KEMISKINAN MELALUI PENDEKATAN SUSTAINABLE DEVELOPMENT GOALS PADA MASYARAKAT KEDAH MALAYSIA - Sylvina Rusadi; Farahiyah Binti Fadzil; Evi Zubaidah (Universitas Mataram, 2023)
Women have an important role in their position in household life, but this is often used as the main cause of women having limitations in other fields such as the economy, education and even politics. Kedah State is one of the areas in Malaysia which is the location for international scale community service activities. This activity was held to see how far the role of women's empowerment is involved in achieving the Sustainable Development Goals on poverty. For this reason, this community service activity will provide a solution for the Kedah community with the aim of providing knowledge to partners regarding women's empowerment in increasing economic, social and cultural values ​​and efforts that can be made to increase it. The method used in this community service is through socialization, delivery of material and discussion, and answer directly to the community. The results obtained from this activity are the lower ability of women than men, the existence of cultural involvement in society and the lack of functioning of the role of local community institutions. Community service activities carried out in the form of outreach to women's groups in Kampung Singkir Kedah Malaysia were able to provide knowledge and understanding of the importance of women's role in improving the family economy by improving self-quality through good social interaction and education.